2015
DOI: 10.1159/000435919
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Intracranial Hypertension in the Northwest of Northern Ireland: Epidemiology and Clinical Management

Abstract: Background: There is limited literature on the epidemiology of idiopathic intracranial hypertension (IIH). The diagnosis and management of IIH require a multidisciplinary approach. We sought to study the incidence as well as prevalence of IIH and to evaluate the current management of IIH in the northwest of Northern Ireland. Methods: Medical records of patients diagnosed with IIH between 2007 and 2014 in a general hospital in Northern Ireland were reviewed. Clinical and outcome data were retrieved. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
3
22
0
1
Order By: Relevance
“…2,3,5 Additional studies from Japan and Italy have found a much lower incidence, 0.03 in Japan 6 and 0.3 in Italy per 100 000 inhabitants, respectively. 2,3,5 Additional studies from Japan and Italy have found a much lower incidence, 0.03 in Japan 6 and 0.3 in Italy per 100 000 inhabitants, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…2,3,5 Additional studies from Japan and Italy have found a much lower incidence, 0.03 in Japan 6 and 0.3 in Italy per 100 000 inhabitants, respectively. 2,3,5 Additional studies from Japan and Italy have found a much lower incidence, 0.03 in Japan 6 and 0.3 in Italy per 100 000 inhabitants, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…The annual incidence of IIH ranged from 0.9-2.4 per 100 000 individuals in three large-scale studies performed in the USA, Libya and Northern Ireland. 2,3,5 Additional studies from Japan and Italy have found a much lower incidence, 0.03 in Japan 6 and 0.3 in Italy per 100 000 inhabitants, respectively. 7 Several risk factors and co-morbidities have been reported to be associated with IIH and summarized in a meta-analysis by Chen et al 8 However, due to rareness of IIH and few large controlled studies the associations found might be spurious.…”
Section: Introductionmentioning
confidence: 96%
“…A recent epidemiology study reported an incidence of IIH occurring in 28/100 000/year,6 which is the highest reported rate in the literature so far 7. In the USA, there was a 320% increase in new cerebrospinal fluid (CSF) shunt procedures for IIH between 1998 and 2002 8.…”
Section: Introductionmentioning
confidence: 99%
“…The annual incidence of IIH is approximately 3/100,000 persons and it is usually seen in young obese women (1,2). The major morbidities are headache and vision loss if the disease cannot be diagnosed or the treatment is delayed (3).…”
Section: Introductionmentioning
confidence: 99%